Uncovering the (un)attended: Pupil light responses index persistent biases of spatial attention in neglect - Ten Brink, AF; Van Heijst, Marlies; Portengen, Brendan; Naber, Marnix; Strauch, Christoph (Masson SpA, 2023)
Visuospatial neglect is a frequent and disabling disorder, mostly after stroke, that presents in impaired awareness to stimuli on one side of space. Neglect causes disability and functional dependence, even long after the injury. Improving measurements of the core attentional deficit might hold the key for better understanding of the condition and development of treatment. We present a rapid, pupillometry-based method that assesses automatic biases in (covert) attention, without requiring behavioral responses. We exploit the phenomenon that pupil light responses scale with the degree of covert attention to stimuli, and thereby reveal what draws (no) attention. Participants with left-sided neglect after right-sided lesions following stroke (n = 5), participants with hemianopia/quadrantanopia following stroke (n = 11), and controls (n = 22) were presented with two vertical bars, one of which was white and one of which was black, while fixating the center. We varied which brightness was left and right, respectively across trials. In line with the hypotheses, participants with neglect demonstrated biased pupil light responses to the brightness on the right side. Participants with hemianopia showed similar biases to intact parts of the visual field, whilst controls exhibited no bias. Together, this demonstrates that the pupil light response can reveal not only visual, but also attentional deficits. Strikingly, our pupillometry-based bias estimates were not in agreement with neuropsychological paper-and-pencil assessments conducted on the same day, but were with those administered in an earlier phase post-stroke. Potentially, we pick up on persistent biases in the covert attentional system that participants increasingly compensate for in classical neuropsychological tasks and everyday life. The here proposed method may not only find clinical application, but also advance theory and aid the development of successful restoration therapies by introducing a precise, longitudinally valid, and objective measurement that might not be affected by compensation.
Keywords: Covert attention; Hemianopia; Pupillometry; Spatial attention; Unilateral neglect; Experimental and Cognitive Psychology; Neuropsychology and Physiological Psychology; Cognitive Neuroscience